SMaRT lncRNA controls translation of a G‐quadruplex‐containing mRNA antagonizing the DHX36 helicase. (26th April 2020) - Martone, Julie; Mariani, Davide; Santini, Tiziana; Setti, Adriano; Shamloo, Sama; Colantoni, Alessio; Capparelli, Francesca; Paiardini, Alessandro; Dimartino, Dacia; Morlando, Mariangela; Bozzoni, Irene
Abstract: Guanine‐quadruplexes (G4) included in RNA molecules exert several functions in controlling gene expression at post‐transcriptional level; however, the molecular mechanisms of G4‐mediated regulation are still poorly understood. Here, we describe a regulatory circuitry operating in the early phases of murine muscle differentiation in which a long non‐coding RNA (SMaRT) base pairs with a G4‐containing mRNA (Mlx‐γ) and represses its translation by counteracting the activity of the DHX36 RNA helicase. The time‐restricted, specific effect of lnc‐SMaRT on the translation of Mlx‐γ isoform modulates the general subcellular localization of total MLX proteins, impacting on their transcriptional output and promoting proper myogenesis and mature myotube formation. Therefore, the circuitry made of lnc‐SMaRT, Mlx‐γ, and DHX36 not only plays an important role in the control of myogenesis but also unravels a molecular mechanism where G4 structures and G4 unwinding activities are regulated in living cells. Synopsis: This study shows that muscle‐specific lnc‐SMaRT regulates early myogenesis. By base‐pairing to the G4 region present in the Mlx‐γ mRNA, lnc‐SMaRT controls its translation in an antagonistic manner to the RNA helicase DHX36. The Mlx‐γ mRNA, encoding a myogenic regulator, contains a G4 region and requires the DHX36 helicase for translation. lnc‐SMaRT prevents Mlx‐γ translation by base pairing to the G4 region and antagonizing DHX36 function. lnc‐SMaRT mediated regulation of Mlx‐γ modulates the subcellular localization of other MLX protein isoforms, thereby affecting their transcriptional activity in myogenesis. Abstract : This study shows that muscle‐specific lnc‐SMaRT regulates early myogenesis. By base‐pairing to the G4 region present in the Mlx‐γ mRNA, lnc‐SMaRT controls its translation in an antagonistic manner to the RNA helicase DHX36.